Variability in seedling water status during drought within a Quercus ilex subsp. ballota population, and its relation to seedling morphology (Forest Ecology and Management, 1998)
Differences in morphology, growth and plant water status during drought were studied in greenhouse-grown Quercus ilex subsp. ballota seedlings produced by different mother trees occurring in a savannah-like forest (locally named dehesa) in southern Spain. There were signi®cant differences among mother trees in the biomass of their seeds (mother tree level accounted for 62% of total variance in this trait), in the percentage of seedlings that emerged and in the time of shoot emergence. The progeny that had high emergence rates (80±90%) also had short emergence times while the opposite was true for the progeny that had low (43%) and intermediate (70%) emergence rates. Acorn biomass covaried signi®cantly with seedling total biomass and with the biomass of different parts of the seedlings, but not with the partitioning of biomass among roots and shoots (root/shoot ratio) nor to morphological seedling traits such as shoot height, total leaf area, average leaf size, speci®c leaf area (SLA) and leaf number. All these traits varied signi®cantly among the seedlings produced by different mother trees. The conductance to water vapour (glw) of the foliage of the seedlings also varied signi®cantly among mother trees and was dependent on the root/shoot ratio as on the total leaf area of the seedlings, but not on the total seedling biomass. One of the six trees that were studied produced seedlings which had a signi®cantly higher root/shoot ratio, smaller leaf area, smaller leaves, higher speci®c leaf area and shorter stems than the seedlings produced by any other tree. In addition, the former set of seedlings had signi®cantly higher glw 15 and 30 days after drought, and higher leaf water content at the end of the experiment than the other seedlings. We discuss the value of using single seedling traits related to drought tolerance such as root/shoot ratio and leaf area in the framework of the restoration of savannah-like oak forest in the Mediterranean areas. We also discuss the functional implications of the diversity of genotypes within the oak populations in the framework of the global climate change